IMPACTS OF THE TECHNOLOGY ACCEPTANCE MODEL (TAM) ON THE USE OF THE TIKTOK E-COMMERCE APPLICATION AMONG INDONESIAN STUDENTS - Syafika, Yusinda Zarah; Antonio, Gregorius Rudy (UTSAHA: Journal of Entrepreneurship, 2024)
The Technology Acceptance Model (TAM) explains how people's cognitive perceptions and behavior are formed when they use and accept technology. This study focuses on three main components that influence the acceptance and use of TikTok Shop. These factors are Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Attitude towards Using (ATU). This study aims to investigate how the Technology Acceptance Model (TAM) impacts university students' use of the TikTok Shop feature in Indonesia. Data was collected through a questionnaire sent via Google Forms and included 102 students from various universities throughout Indonesia who had previously used TikTok Shop every day. SmartPLS checks the hypothesis using Structural Equation Modeling (SEM). The research findings indicated that students' perceptions of the utility of the TikTok Shop are significantly and positively influenced by their perceptions of the shop. Ease of use of the platform substantially influences the usefulness of the platform and students' attitudes towards it. In addition, ease of use of the platform indirectly influences students' perspectives through the influence of perceived benefits. Students' evaluations of the usability and convenience of TikTok Shop significantly influence their attitudes and willingness to use the website.  This study also provides insight into the critical components that determine the acceptance and use of e-commerce platforms based on social media. The practical implications of this research relate to suggestions for improving the creation of e-commerce platforms, encouraging a more favorable disposition for their users.